Hepatitis B vaccines: assessment of the seroprotective efficacy of two recombinant DNA vaccines - Coates, Toby; Wilson, Rosamund; Patrick, Guy; André, Francis; Watson, Virginia (Clinical therapeutics, 2001)
Background: In universal vaccination programs, when there is no postvaccination serologic assessment of response, there must be confidence that the vaccines used provide a high degree of seroprotection. Objective: This parallel analysis of 2 recombinant hepatitis B vaccines (Engerix B ® and Recombivax ®/HB-Vax II ®) was conducted to review the seroprotective efficacy of each vaccine in defined populations. Methods: Clinical studies of the 2 vaccines published as manuscripts or conference abstracts in the public domain between January 1986 and April 1999 were identified retrospectively by unrestricted screening of journals through BIOSIS ®, MEDLINE ®, and EMBASE ® and the Internet. Unpublished or internal company data were excluded to maintain impartiality. The studies were reviewed and analyzed. The studies were not assessed for quality other than a judgment of their eligibility for inclusion in the analysis. The primary outcome measure was the proportion of subjects in defined populations who showed an early seroprotective response to currently licensed vaccination schedules. Summary statistical analyses of seroprotective response rates and 95% CIs were calculated for each vaccine for each population. Seroprotective response was defined by an anti-hepatitis B surface antigen titer ≥ 10 IU/L measured between 1 and 3 months after the final vaccination. Because the study was designed specifically to review published immunogenicity data, safety data were not assessed. The study was not designed to demonstrate superiority of one vaccine over the other. Results: A total of 181 clinical studies representing 32,904 vaccinated subjects were reviewed and analyzed, of whom 24,277 had been vaccinated with Engerix B and 8627 vaccinated with Recombivax/HB-Vax II. Seroprotection was achieved in 20,060 subjects (95.8%) with Engerix B and in 7774 subjects (94.3%) with Recombivax/HB-Vax II in the normal population vaccinated according to currently licensed 3-dose schedules. In a sub-group analysis, response rates in health care workers were 6492 subjects (94.5%) for Engerix B and 3245 subjects (92.2%) for Recombivax/HB-Vax II. Children and adolescents (1–19 years) showed the highest response rates to vaccination (4612 [98.6%], Engerix B; 2292 [98.9%], Recombivax/HB-Vax II). A total of 2875 infants (<1 year) (95.8%) achieved seroprotection with Engerix B; 701 (88.5%) achieved seroprotection with Recombivax/HB-Vax II. Conclusions: Hepatitis B vaccination programs using either Engerix B or Recombivax/HB-Vax II can achieve high seroprotective response rates, particularly in childhood and adolescence. Ideally, younger populations should be a primary target in current universal vaccination programs.